Production and Purification of Laccase enzyme by Trichoderma viride (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
The ability of Trichoderma viride to synthesize extracellular enzymes (Lacase enzyme) using a substrate that contains media was examined. This isolate generated laccase at its greatest level (0.166U/ml) in liquid medium.  This study was  demonstrated the production, purification, and characterisation of the laccase enzyme from T.viride. The results showed that 96 hours was the optimum period of time for Laccase to incubate from this fungus. Laccase displayed the maximum level of activity at pH 4.5 and temperature 30 °C. The results revealed that the best ratio for laccase precipitation was 90%  by using ammonium sulphate.  In addition, for the purification of laccase enzyme, one peak of Laccase was appeared  in gel filtration purified from T.viride, while 2 peaks of Laccase were seen in ion exchange chromatography. According to the findings, the molecular weight of T. viride Laccase using SDS-PAGE was roughly 66KD under denaturation conditions.